Taṭbīq Kitāb al-Ṣarf al-Muyassar bi al-Madkhal al-‘Ilmī bimarkaz Tarqiyyah al-Lugah al-‘Arabiyyah - Ulum, Moh.; Hasanah, Maidatul (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This development research aims to determine the process of preparing textbooks with a scientific approach, measuring the validity and effectiveness of using the book. The method used in this research is qualitative & quantitative research using Addie's approach; the researcher conducted a needs analysis and collected data related to preparing textbooks. Then this jar book was validated by experts & analyzed using the Likert Scale formula. Then a trial was carried out to prepare teaching materials with the pretest & post-test approach. Pretest & post-test results were analyzed using the t-test to measure its effectiveness. The results of the study show that textbooks are feasible to use. Based on the validity of the experts, This textbook gets a score of 87.2% from book experts, and gets a score of "very good," with a score of 95% from language experts, then gets a score of "very good," with a score of 98.8% from design experts. Then, a pretest and post-test were carried out to measure the effectiveness of using this book and obtained a score of 9.18%. This means that the pretest and post-test results are greater than the T-theory value (in the table), which is 2.11, with a significance level ratio of 0.05 (5%). %). The use of this textbook received appreciation from eighteen students of the PP Nurul Jadid Arabic Language Development Institute (LPBA), where the results obtained were 99% and were at the "very good" level. Students at the Nurul Jadid Arabic Language Development Institute (LPBA) enjoy the learning process using this book and find it easy to understand the material.